MENINGKATKAN KEMAMPUAN GURU DALAM MEMBUAT PROPOSAL PENELITIAN TINDAKAN KELAS PADA MTS BINAAN MELALUI WORKSHOP - Hidayati, Prihatini (Universitas Muhammadiyah Prof Dr Hamka, 2019)
This research aims to describe the process of creating Class Action Research proposal through a workshop, and also to improve teacher skill of creating Class Action Research through a workshop in Jakarta. Furthermore, the objective of this research is to describe the respond of teacher towards activities performed. This research is classified as supervisory action research by involving 25 teacher. The research has done with two cycle and each cycle contained of four stages: planning, execution, observation and reflexion. Indicator of performance that have been set is if there are at least 80% teacher classified to very good and good in aspect of assessing Class Action Research, then it can be said that the action is successful. Measured aspect in assessing successful of this action is the readiness of teacher following the workshop and score of workshop execution. From the result, obtained that there are increases of teacher skill in creating Class Action Research from cycle 1 until cycle 2. Therefore, it can be concluded that workshop can increase teacher skill in creating Class Action Research proposal at MTs in Jakarta. Therefore, it can be suggested that workshop can be used as an alternative to increase teacher skill in creating Class Action Research.